Vegucated [videorecording (DVD)] - Wolfson, Marisa Miller (Kind Green Planet, 2010)
"Vegucated is a feature-length documentary that follows three meat- and cheese-loving New Yorkers who agree to adopt a vegan diet for six weeks. Lured with true tales of weight lost and health regained, they begin to uncover hidden sides of animal agriculture and soon start to wonder whether solutions offered in films like Food, Inc. go far enough. Before long, they find themselves risking everything to expose an industry they supported just weeks before. But can their conviction carry them when times get tough? Part science class, and part adventure story, this entertaining documentary showcases the rapid and at times comedic evolution of three people who share one journey and ultimately discover their own paths in creating a kinder, cleaner, greener world, one bite at a time.